Seven theses of an expert panel in emergency medical services addressed to policy makers and society Fürther Gespräche: Expertenforum für den Rettungsdienst mit Forderungen an Politik und Gesellschaft - Meyer, Klaus; Dormann, Harald; Prescher, Thomas (Notfall und Rettungsmedizin, 2024)
Emergency medical services, the training of paramedics, and the legal requirements in Germany do not currently offer a good framework for the future. A German expert panel that included persons from the fields of science, education, emergency medicine, and emergency medical services discussed potential developments and further professionalization strategies. The central results of the “Fürther Gespräche” are summarized in the following seven theses: requirements and medical care needs, prevention (e.g., by contacting frequent callers) and implementation of extended care components, a digitalization strategy, integrated emergency medical dispatch centers and networked health services, personnel development, qualification levels, and emergency physician qualifications (and deployment strategies).
CRIS-Team Scopus Importer:2025-02-03
Keywords: Digitalization; Emergency medical dispatch centers; Emergency medical services; Emergency medicine; Emergency physicians; Paramedics